Using District Health Information System (DHIS2) for Health Data Integration in Special Region of Yogyakarta - Ni'mah Hanifah; Guardian Yoki Sanjaya; Nuryati Nuryati; Aprisa Chrysantina; Niko Tesni Saputro; Mardiansyah Mardiansyah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
A number of applications have been used for managing health data and information and tend to be fragmented between health programs in health offices. In consequence, the analysis and interpretation process becomes difficult since the data is scattered in separate sources. One of the solutions offered as an effort to synchronize and integrate health data in Indonesia is through implementing District Health Information Software (DHIS2). DHIS2 is an application that emphasizes data integration at the health office level. Faculty of Medicine, Public Health and Nursing UGM has been partnered with the Special Region of Yogyakarta Health Office to carry out community service activities in the context of utilizing DHIS2 for health data integration in the province. The implementation of DHIS2 was divided into 4 stages, namely workshop on data availability, socialization, and training of DHIS2; data mapping and customizing DHIS2; implementing health data integration; and dissemination, supervision, and evaluation. Six health offices were the target of community service activities in the province. DHIS2 has facilitated health office staff to analyse and visualize health information that is used for decision making and advocacy. This community service activity supports the government’s efforts to provide one-stop data and contributes to strengthening health information systems both nationally and regionally.